Nuturing Innovation : Venture Acceleration Networks, A Review of Existing Models - World Bank (Washington, DC, 2013)
This report evaluates the role, operational models and identifies good practices of programs that seek to accelerate innovative entrepreneurship by managing, nurturing and leveraging social and business networks. The report discusses the role of venture acceleration networks, using networks to support entrepreneurs, creating strong networks, selecting ventures, financing the program, choosing an organizational structure, adapting to the innovation ecosystem and the role for the public sector in Russia. The second part of the report describes individual programs. The conclusion suggests next steps for operationalizing a venture acceleration network in Russia. Venture acceleration network experiments highlight a multitude of challenges. Some face challenges linked to the environments where they operate. Where there is no local pipeline of coachable ventures or of mentors with the right mix of skills, experience and connections, programs do not succeed. Programs also face an uphill challenge where there is no local access to complementary forms of public and private support.